2021
DOI: 10.3389/fgene.2021.743786
|View full text |Cite
|
Sign up to set email alerts
|

SOCS3 is Related to Cell Proliferation in Neuronal Tissue: An Integrated Analysis of Bioinformatics and Experiments

Abstract: Glioma is the most common primary malignant tumor that occurs in the central nervous system. Gliomas are subdivided according to a combination of microscopic morphological, molecular, and genetic factors. Glioblastoma (GBM) is the most aggressive malignant tumor; however, efficient therapies or specific target molecules for GBM have not been developed. We accessed RNA-seq and clinical data from The Cancer Genome Atlas, the Chinese Glioma Genome Atlas, and the GSE16011 dataset, and identified differentially exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…One of the upregulated genes, SOCS3 , has been reported to be associated with the proliferation of neural tissue. 57 Expression of clusterin, a stress-related gene that promotes cell survival, 58 was also increased. Additionally, several upregulated genes, such as shisa5 and BCL3 , were identified, and their biological processes were reported but their relationships with RGCs were not.…”
Section: Discussionmentioning
confidence: 99%
“…One of the upregulated genes, SOCS3 , has been reported to be associated with the proliferation of neural tissue. 57 Expression of clusterin, a stress-related gene that promotes cell survival, 58 was also increased. Additionally, several upregulated genes, such as shisa5 and BCL3 , were identified, and their biological processes were reported but their relationships with RGCs were not.…”
Section: Discussionmentioning
confidence: 99%
“…As aforementioned above, siRNA was used for transfection and Western blotting was performed to verify the knockdown efficiency. Numerous studies have revealed that SOCS3 expression is closely associated with the proliferation of tumour cells 33,34 . The current study used SOCS3 as a marker of cell proliferation for knockdown experiments, and detected PCNA expression by Western blotting, which revealed that the expression level of PCNA was reduced (Figure 12A).…”
Section: Resultsmentioning
confidence: 82%
“…It has also been found that EYA2 is downregulated in hepatocellular carcinoma (HCC), and EYA2 can regulate SOCS3 expression in combination with DACH1 transcription, thereby inhibiting HCC progression via SOCS3 ‐mediated blockade of the JAK/STAT signalling pathway 44 . Current studies have found that the high expression of SOCS3 can promote the proliferation of GBM cells 34 . Therefore, we want to further study the other functions of SOCS3 , including migration and invasion, and explore the potential mechanisms of SOCS3 's possible regulatory role by bioinformatics analysis, so as to prepare for further exploration of SOCS3 mechanisms in GBM in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The recent emergence of high throughput sequencing and proteomics analysis has enhanced the understanding of glioma biology and also aided in the identification of novel biomarkers [ 55 ]. Numerous studies have utilized gene expression datasets from TCGA, CGGA etc., to identify potential prognostic biomarkers in glioma such as GINS4 [ 56 ], SOCS3 [ 57 ], PTPRN [ 58 ], PLAT, IGFBP2, BCAT1, SERPINH1 [ 59 ], MAGEH1 [ 55 ] etc. Some of these markers have also been validated further in the patient cohort and also by functional analysis [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have utilized gene expression datasets from TCGA, CGGA etc., to identify potential prognostic biomarkers in glioma such as GINS4 [ 56 ], SOCS3 [ 57 ], PTPRN [ 58 ], PLAT, IGFBP2, BCAT1, SERPINH1 [ 59 ], MAGEH1 [ 55 ] etc. Some of these markers have also been validated further in the patient cohort and also by functional analysis [ 56 , 57 ]. The same datasets have been used in the present study to establish the utility of PTMA as an independent predictor of patient survival.…”
Section: Discussionmentioning
confidence: 99%